PAJAK DAERAH, DAU, DAN DAK TERHADAP KEMANDIRIAN KEUANGAN DAERAH: SUATU PERANAN BELANJA MODAL - Fathan Qoriiba, (2021)
This study aims to examine the effect of variable Local Tax, General Allocation Fund, Special Allocation Fund, and Capital Expenditure as intervening variables on Regional Finance Independence. Districts/municipalities in West Java Province were used as samples in this study. This study used a sample of 27 districts/municipalities in West Java Province 2016-2019 using the purposive sampling method. A sample of 27 regencies/cities in West Java Province was obtained with a total of 108 samples. In this study, secondary data was used from the Examination Report the Result of the Examination on Local Government Financial Report issued by BPK. The hypothesis in this study was tested using the Structural Equation Model (SEM) using the SmartPLS 3.0 software. This study resulted in Local Tax, General Allocation Fund, and Special Allocation Fund significant effect on Regional Finance Independence, while Capital Expenditure were unable to mediate the effects of Local Tax, General Allocation Fund, and Special Allocation Fund on Regional Finance Independence.